L'engendrement des choses: des hommes, des femmes et des techniques - Chabaud-Rychter, Danielle; Gardey, Delphine (Histoire des sciences, des techniques et de la médecine, 2002)
"Le monde contemporain est marqué par une amplification des biens et des choses, des techniques et des artefacts ; toutes choses nous semblant à la fois ordinaires, évidentes et neutres. Cette modernité est rarement interrogée du point de vue des hommes et des femmes qui la vivent. Pourquoi en effet prêter des intentions aux choses? Elles participent de nos vies, pourvoient à nos besoins, nous soulagent de bien des tâches. Remettre en question la neutralité des techniques est pourtant une bonne façon de s'interroger sur les rapports sociaux de sexes, en se demandant pourquoi les femmes sont durablement exclues de certains domaines techniques ; quel pouvoir confère la maîtrise des techniques ; quel est l'enjeu politique et symbolique de cette maîtrise ; et, au bout du compte, comment les techniques contribuent à ordonner le social, et en particulier les relations sexuées."
Keywords: 1900-1999; 1980-1989; 1990-1999; 2000 à aujourd'hui; 2000-2009; approches et analyses; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; privilèges; périodes historiques; rapports sociaux de sexe; régions géographiques; santé; sciences humaines; sexisme; soc2051; sociologie; systèmes d'oppressions; thématiques

From Social Construction to Social Justice: Transforming How We Teach about Intersexuality - Koyama, Emi; Weasel, Lisa (Women's Studies Quarterly, 2002)
Keywords: LGBTQIA2+; approches et analyses; capacitisme; corps; cours; discipline; intersexuation; justice sociale; premier cycle; pédagogie; santé; sciences humaines; soc2014; systèmes d'oppressions; thématiques; violences; violences médicales; études critiques du handicap

Le mouvement gai et lesbien américain face au SIDA - Marche, Guillaume (L'Homme & la Société, 2002)
Divided between essentialism and constructivism, the mobilization of united-statesian homosexuals becomes a real social movement when it goes beyond the opposition between integrationism and differentialism. Thanks to a complex identity forged by ACT-UP, it has been able in this way to resist AIDS. A comparison between San Francisco and New York shows that the initiative comes from the bottom up. Collective action is most effective as it takes account of differences (such as ethnicity) between homosexuals. This requirement has been dictated by the evolution of AIDS since the 1990s. It is, therefore, in stressing the subjectivity of the actors that the gay and lesbian movement can continue and contribute to social change in the United States.
Keywords: 1900-1999; 1990-1999; LGBTQIA2+; amérique du nord; amériques; approches et analyses; cours; discipline; discours dominant; histoire et politique; homophobie; hétérosexisme; identités LGBTQIA2+; lesbianisme; premier cycle; périodes historiques; queer; régions géographiques; santé; sexualité; shm4000; systèmes d'oppressions; thématiques; états-unis

Gender equity and socioeconomic inequality: a framework for the patterning of women's health - Moss, Nancy E (Social Science & Medicine, 2002)
This paper explores the interrelationship of gender equity and socioeconomic inequality and how they affect women's health at the macro- (country) and micro- (household and individual) levels. An integrated framework draws theoretical perspectives from both approaches and from public health. Determinants of women's health in the geopolitical environment include country-specific history and geography, policies and services, legal rights, organizations and institutions, and structures that shape gender and economic inequality. Culture, norms and sanctions at the country and community level, and sociodemographic characteristics at the individual level, influence women's productive and reproductive roles in the household and workplace. Social capital, roles, psychosocial stresses and resources, health services, and behaviors mediate social, economic and cultural effects on health outcomes. Inequality between and within households contributes to the patterning of women's health. Within the framework, relationships may vary depending upon women's lifestage and cohort experience. Examples of other relevant theoretical frameworks are discussed. The conclusion suggests strategies to improve data, influence policy, and extend research to better understand the effect of gender and socioeconomic inequality on women's health.
Keywords: approches et analyses; projet charge mentale; ressource en ligne; santé; santé des femmes*; sexisme; stéréotypes de genre; systèmes d'oppressions; thématiques; violences; violences économiques

Policing the national body: Sex, race, and criminalization - Silliman, Jael Miriam; Bhattacharjee, Anannya; Davis, Angela Y.; Committee on Women, Population, and the Environment (South End Press, 2002)
Keywords: amériques; approches et analyses; corps; environnement; justice reproductive; maternité; nationalisme; racisme; régions géographiques; santé; sexisme; sofia; système colonial; systèmes d'oppressions; thématiques; états-unis